Enhancing Accounting Use in MSMEs through Experience, Knowledge, and Education: Meningkatkan Penggunaan Akuntansi di UMKM melalui Pengalaman, Pengetahuan, dan Pendidikan - Marita, Tya Ayu; Nurasik, Nurasik (Indonesian Journal of Law and Economics Review, 2024)
This study examines the influence of length of business, accounting knowledge, and level of education on the use of accounting information in micro, small, and medium enterprises (MSMEs) in Ponti Sidoarjo. Using a descriptive quantitative approach and multiple linear regression analysis on data collected from 50 respondents through questionnaires, the research finds that the length of business significantly affects the use of accounting information, indicating longer-established businesses are more likely to utilize it effectively. Additionally, accounting knowledge and level of education positively influence the use of accounting information in these MSMEs. The findings highlight the importance of considering these factors collectively in enhancing accounting practices and decision-making in Ponti Sidoarjo's MSME sector, offering insights for policymakers and stakeholders to develop targeted interventions and educational programs for economic growth and sustainability. Highlight : Length of Business: Experience significantly influences accounting information use in MSMEs. Accounting Knowledge: Expertise enhances effective use of accounting information in MSMEs. Education Level: Higher education positively impacts accounting information utilization in MSMEs. Keyword : Length of Business, Accounting Knowledge, Education Level, Accounting Information, MSMEs